Building Defects Investigation - Two Case Studies On Steel And Reinforced Concrete Structures - Jamaluddin, Norwati (Journal of Structural Monitoring and Built Environment, 2024)
The purpose of this paper is to present two case studies involving the initial assessment of potential causes of building structures that are in doubt. The investigation involving a fertilizer-manufacturing building and residential buildings. The corrosion problems that occurred in the industrial building were severe, and necessitating an assessment to gauge the building's safety condition. For the residential building, a visual inspection was conducted not only on the residential structures themselves but also on the surrounding infrastructures, in order to justify whether the nearby construction works were responsible for the problems. From the investigation on the industrial building, corrosion seems to be the primary problem and a potential cause of structural instability. The severity can be seen as most of the steel structural elements exhibited signs of material loss from their surfaces. From the evaluation through visual inspection and tests, the aggressive environment and insufficient maintenance are the main contributors to the corrosion related damage. Concerning the residential building, based on the inspection of the nearest infrastructures, no fractures were identified that could be attributed to the nearby construction works. Therefore, it may seem that the on-going project may not have affected the existing residential housing located nearby.